Florida's Pesticidal Substances Exempt from the Federal Insecticide, Fungicide, and Rodenticide Act (FIFRA-Section 25(b)) - Frederick M. Fishel (EDIS)
Effective in 1996, the Environmental Protection Agency (EPA) exempted products containing 31 pesticidal active ingredients and 160 inert ingredients from FIFRA regulation. The EPA concluded that the exemption of these products would not pose unreasonable risks to public health or the environment. This document is PI-55, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2005.